Young Consumers’ Intention to Engage in The Sustainable Consumption through Sharing Economy: A Sociotechnical Approach - Qamarani, Syabibah Yusrina; Iqbal, Mohammad; Fahrudi, Agung Nugroho Luthfi Imam (Wacana Journal of Social and Humanity Studies, 2023)
The paper seeks to investigate the influences of sociotechnical aspects on young Indonesian consumers' intentions "to engage in sustainable consumption through the sharing economy." A self-reported online survey on ridesharing use among young customers in Indonesia was undertaken. "A total of 251 valid responses" were obtained. "Structural equation modeling" was used to test the research model empirically. The findings revealed that users' intentions "to engage in sustainable consumption through the sharing economy" were significantly predicted by economic benefit, knowledge, technology fit, information quality, and social aspects. This research fills "gaps in the sharing economy literature" by investigating the effects of sociotechnical factors on young Indonesian consumers' "intention to engage in sustainable consumption through the sharing economy." The findings gave practitioners insights into increasing Indonesian young consumers' propensity to engage in sustainable consumption provided by the sharing economy. Keywords: sharing economy, collaborative consumption, sustainable consumption, sociotechnical framework, peer-to-peer ridesharing, Grab, Gojek